Weak Form Efficient Market Hypothesis And Calendar Effect in LQ 45 Index of Indonesia Stock Exchange Market in 2009-2014 - admin, Ricky Gusvianto B12112019 (Jurnal Manajemen Update, 2016)
The paper attempts to investigate the validity of the Efficient Market Hypothesis and existence of calendar effect on the Indonesia Stock Exchange Market. Initially, the paper discusses the types of the EMH, as also the literature available regarding this topic. Taking a sample of twenty one securities listed in LQ 45 Index on the Indonesia Stock Exchange Market (IDX), this paper applies non parametric tests which are Run test, Kruskal-Wallis test, Mann-Whitney test and this paper also applies parametric test which are series correlation test, One-way Anova test and independent t-test two sample.Based on the results of the test of this paper, it can be concluded that Weak Form Efficient Market exists in LQ 45 Index of IDX while for Day of the Week Effect and Month of the Year Effect are not found to exist in LQ 45 Index of IDX. In conlusion, it is observed that the effect of stock prices for the sample companies on future prices is very meager and an investor cannot reap profits by using the historical share price data as the current share prices already reflect the effect of past share prices data.Keywords : Efficient Market Hypothesis, Indonesia Stock Exchange Market, LQ 45 Index, non-parametric test, parametric test.